The new feminist criticism: essays on women, literature and theory - Carmen Rosa Caldas (Ilha do Desterro)
This book is a collection of eighteen major essays on feminist criticism, which is basically concerned with the literary representations of sexual difference and establishes gender as a fundamental category of literary analysis. According to Showalter, the assumptions of literary study have been totally modified in the last decade due to the impact of the feminist critical revolution. This important approach to literature has "opened a space for the authority of the woman critic that extends beyond the study of women's writing to the reappraisal of the whole body of texts" (p.3).